2016
DOI: 10.1308/rcsann.2016.0292
|View full text |Cite
|
Sign up to set email alerts
|

Parietex™ Composite mesh versus DynaMesh®-IPOM for laparoscopic incisional and ventral hernia repair: a retrospective cohort study

Abstract: INTRODUCTION Laparoscopic incisional and ventral hernia repair (LIVHR) is widely accepted and safe but the type of mesh used is still debated. We retrospectively compared postoperative outcomes with two different meshes commonly used in LIVHR. METHODS This is a retrospective study of patients who underwent incisional hernia repair between January 2008 and December 2010. Two meshes were used: Parietex™ Composite (Covidien, New Haven, CT, USA) and the DynaMesh®-IPOM (FEG Textiltechnik mbH, Aachen, Germany). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…A more recent prospective study by Sommer et al demonstrated a 6% reoperation rate after a median follow-up of 36 months, and although some reoperations were because of adhesions, the majority were reoperations for a symptomatic recurrence [ 26 ]. In a retrospective study on 88 patients undergoing laparoscopic ventral hernia repair, Tandon et al compared 62 Parietex™ Composite meshes and 26 DynaMesh® IPOM meshes [ 27 ]. With a median follow-up of 53.6 months, they found a recurrence rate of 12.9 and 3.8%, respectively, for Parietex™ Composite and DynaMesh® IPOM.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent prospective study by Sommer et al demonstrated a 6% reoperation rate after a median follow-up of 36 months, and although some reoperations were because of adhesions, the majority were reoperations for a symptomatic recurrence [ 26 ]. In a retrospective study on 88 patients undergoing laparoscopic ventral hernia repair, Tandon et al compared 62 Parietex™ Composite meshes and 26 DynaMesh® IPOM meshes [ 27 ]. With a median follow-up of 53.6 months, they found a recurrence rate of 12.9 and 3.8%, respectively, for Parietex™ Composite and DynaMesh® IPOM.…”
Section: Discussionmentioning
confidence: 99%
“…LVHR is now widely accepted for the repair of ventral hernia defects. 17 It has the advantages of a shorter hospital stay, lower incidence of infection, less pain and less risk of adhesion. 17 , 18 There are some common complications following LVHR, including seroma formation, ileus, pain and wound infection.…”
Section: Discussionmentioning
confidence: 99%
“… 17 It has the advantages of a shorter hospital stay, lower incidence of infection, less pain and less risk of adhesion. 17 , 18 There are some common complications following LVHR, including seroma formation, ileus, pain and wound infection. 19 More serious complications include bowel injury, which is higher in LVHR than OVHR.…”
Section: Discussionmentioning
confidence: 99%
“… Type of material Chemical name of material Ref. 1 A: Non-absorbable synthetic materials Polypropylene (PP) [ 22 ] 2 Polytetrafluoroethylene (PTFE) [ 23 ] 3 Expanded polytetrafluoroethylene (ePTFE) [ 24 ] 4 Polyvinylidene fluoride (PVDF) [ 24 ] 5 Polyethylene terephthalate (PET) [ 23 ] 6 nylon 6 [ 25 ] 7 Polycarbonate polyurethane urea [ 26 ] 8 Cross-linked acrylic polymer [ 27 ] 9 Polycaprolactone (PCL) based poly (urethane urea) (PUU) [ 28 ] 10 expanded polytetrafluoroethylene (ePTFE) reinforced with fluorinated ethylene propylene (FEP) [ 29 ] 11 Co-knitted using PP and PVDF [ 30 ] 12 Co-knitted using PP and Polyurethane (PU) [ 31 ] 13 Co-knitted using PP and Polycarbonate polyurethane urea [ 32 ] 14 PP with titanium coa...…”
Section: Hernia Meshmentioning
confidence: 99%
“… Type of material Chemical name of material Ref. 1 Non-absorbable synthetic materials ePTFE [ 65 ] 2 PVDF [ 30 ] 3 Cross-linked acrylic polymer with polyamide [ 27 ] 4 Polyurethane [ 31 ] 5 silicone [ 66 ] 6 Absorbable synthetic materials P (LA-CL) [ 32 , 67 ] 7 P (GA-CL) [ 31 ] 8 P (GA-TMC) [ 40 ] 9 P (GA-CL-TMC-LA) [ 68 ] 10 Oxidized regenerated cellulose (ORC) [ 56 , 69 ] 11 Natural materials Bioabsorbable Oil Fatty Acid (O3FA): fatty acids, lipids and glycerides [ 31 ] 12 Cross-linked resorbable collagen film of porcine origin [ 53 ] 13 Composite materials Porcine collagen, polyethylene glycol (PEG)and glycerol …”
Section: Hernia Meshmentioning
confidence: 99%